Measuring for Success : What CEOs Really Think About Learning Investments - Phillips, Jack; Phillips, Patricia (Association for Talent Development, 2009)
Workplace learning professionals are often frustrated when senior executives and other top organizational leaders do not "get" the value of learning and training initiatives. Often these same professionals are left wondering what "measuring stick" is most meaningful to their company's purse strings holders. Based on interviews, surveys, research, and briefings with senior management and C-Level executives, this book reveals what specific learning measurements are and are not important to top level executives